1985
DOI: 10.1016/0020-7292(85)90027-x
|View full text |Cite
|
Sign up to set email alerts
|

The “Grand Multipara” - Is it a problem? A review of 5785 cases

Abstract: The Grand Multipara (GM) has almost disappeared in the Western countries due to the advancement of family planning. Having a heterogeneous population, the problem of Grand Multiparity still exists in our country. This study is based on 5785 cases of GM which were treated in our Obstetrical Department during a period of 16 years (1960-1975). We have compared this group to the general obstetrical population in terms of pregnancy and delivery complications. Face and breech presentations as well as transverse lie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 2 publications
3
45
0
Order By: Relevance
“…While many antenatal and intrapartum complications like diabetes (overt and gestational), anemia, preterm delivery, malpresentation at term, postpartum hemorrhage, macrosomia showed a significant linear increase with increasing parity as indicated by v 2 test for linear trend (Fig. 1) as also reported by many other studies [3][4][5][6][7][8][9]; there were some, like the need for labor augmentation with its attendant risks specially in women of higher parity and soft tissue injuries, which showed a significantly declining trend with increasing parity as indicated by v 2 test for linear trend (Fig. 2).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…While many antenatal and intrapartum complications like diabetes (overt and gestational), anemia, preterm delivery, malpresentation at term, postpartum hemorrhage, macrosomia showed a significant linear increase with increasing parity as indicated by v 2 test for linear trend (Fig. 1) as also reported by many other studies [3][4][5][6][7][8][9]; there were some, like the need for labor augmentation with its attendant risks specially in women of higher parity and soft tissue injuries, which showed a significantly declining trend with increasing parity as indicated by v 2 test for linear trend (Fig. 2).…”
Section: Discussionsupporting
confidence: 76%
“…Most of the studies in the literature have compared the outcome between women of low parity (parity 2-4) and grand multiparty (parity [5][6][7][8][9], but only few studies have compared the outcome between the three groups as defined by International Federation of Gynecology and Obstetrics: lower parity (parity 2-4), grand multiparity (parity [5][6][7][8][9] and great grand multiparity (parity 10 and above).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast two other studies from Israel reported an increase in classical complications said to be associated with grandmultiparity 5,6 . This difference may be because neither study used aged matched controls and advanced maternal age has been associated with a higher incidence of chronic hypertension, diabetes, and other antepartum complications which may also influence intrapartum events.…”
Section: Grandmultiparae In a Modern Setting 251mentioning
confidence: 73%
“…Hence, grandmultiparity has been defined by the International Federation of Gynecology and Obstetrics (1993) as delivery of the fifth to ninth viable pregnancies 1,2,3,4,5 .Multiparity has been identified as an independent risk factor for a varietyof serious intrapartum complications including: placentaprevia, placental abruption, malpresentation ofthe fetus, instrumented delivery, cesarean delivery,postpartum hemorrhage, prematurity, newborn intensivecare unit admission, and maternal death. 4,[6][7][8][9] -Multiparity‖, from the introduction of the term had been regarded -dangerous‖ and an independent factor in maternal and infantile morbidity and mortality 7,[10][11][12][13][14] . Although some other works tried shifting the blame to other factors including: poor perinatal care 2,6,[15][16][17][18][19], interpopulation differences 20 , poor socio-economic status [23][24][25] as well as advanced maternal age [28][29][30][31] .There has been repeatedly mixed results as various researchers have observed inconsistent outcomes in seemingly similar populations.…”
Section: Introductionmentioning
confidence: 99%